Eliminating mother-to-child transmission of the human immunodeficiency virus in sub-Saharan Africa: The journey so far and what remains to be done - Olatunji O. Adetokunboh; Mojisola Oluwasanu (Elsevier, 2016)
Summary: This review was carried out to provide a comprehensive overview of efforts toward elimination of mother-to-child transmission (MTCT) of human immunodeficiency virus (HIV) with respect to progress, challenges, and recommendations in 21 sub-Saharan African priority countries. We reviewed literature published from 2011 to April 2015 using 3 databases; PubMed, Scopus, and Web of Science, as well as the 2014 Global Plan Progress Report. A total of 39 studies were included. Between 2009 and 2013, there was a 43% reduction in new HIV infections, the final MTCT rate was reduced from 28% to 18%, and antiretroviral therapy (ART) coverage increased from 11% to 24%. Challenges included poor adherence to antiretroviral therapy, poor linkage between mother-child pairs and post-natal healthcare services low early infant diagnosis coverage, low pediatric ART coverage, and high unmet needs for contraceptive services. Future recommendations include identification of key barriers, health system strengthening, strengthening community involvement, and international collaboration. There has been significant progress toward eliminating MTCT of HIV, but more effort is still needed. Keywords: Global Plan, Mother-to-child transmission, HIV, Priority countries, Sub-Saharan Africa